Evaluation of a Multidisciplinary Pain, Agitation, and Delirium Guideline in Mechanically Ventilated Critically Ill Adults. (April 2019) - Heim, Melissa; Draheim, Ryan; Krupp, Anna; Breihan, Paula; O'Rourke, Ann; Wells, Jeffrey; Fish, Jeffrey
Background: A multidisciplinary team updated an institution-specific pain, agitation, and delirium (PAD) guideline based on the recommendations from the Society of Critical Care Medicine (SCCM) PAD guidelines. This institution-specific guideline emphasized protocolized sedation with increased as needed boluses, and nonbenzodiazepine infusions, daily sedation interruption, and pairing of spontaneous awakening (SAT) and breathing trials (SBT).Objective: The purpose of this study was to evaluate the impact of implementation of a PAD guideline on clinical outcomes and medication utilization in an academic medical center intensive care unit (ICU). It was hypothesized that implementation of an updated guideline would improve clinical outcomes and decrease usage of benzodiazepine infusions.Methods: Pre-post retrospective chart review of 2417 (1147 pre, 1270 post) critically ill, mechanically ventilated adults in a medical/surgical ICU over a 2-year period (1 year pre and post guideline implementation).Results: After guideline implementation, average ventilation days was reduced (3.98 vs 3.43 days, P = .0021), as well as ICU and hospital length of stay (LOS) (4.79 vs 4.34 days, P = .048 and 13.96 vs 12.97 days, P = .045, respectively). Hospital mortality (19 vs 19%, P = .96) and acute physiology and chronic health evaluation (APACHE) IV scores (77.28 vs 78.75, P = .27) were similar. After guideline implementation, the percentage of patients receiving midazolam infusions decreased (422/1147 [37%] vs 363/1270 patients [29%], P = .0001). The percentage of patients receiving continuous infusion propofol (679/1147 [59%] vs 896/1270 [70%], P = .0001) and dexmedetomidine (78/1147 [7%] vs 147/1270 [12%], P = .0001) increased.Conclusions: Implementing a multidisciplinary PAD guideline utilizing protocolized sedation and daily sedation interruption decreased ventilation days and ICU and hospital LOS while decreasing midazolam drip usage.